Cardiac parameters during the estrous cycle of canine bitches - de Souza, Rute C.A.; Peres, Regiane [UNESP]; Sousa, Marlos G.; Camacho, Aparecido A. [UNESP] (FapUNIFESP (SciELO), 2017)
The cardiovascular parameters of canine bitches were assessed during the estrous cycle. A total of eleven mongrel female dogs were enrolled in a longitudinal prospective investigation. Six animals were bred during the study and were assigned into group I, in which evaluations were performed during proestrus, estrus, gestational diestrus and anestrus. The five remaining bitches were not bred and underwent evaluations during proestrus, estrus, nongestational diestrus and anestrus. The holter data showed a gradual increase in the minimum and mean heart rate along pregnancy, as well as a reduction during anestrus, which differed significantly among the distinct periods. The values for maximal heart rate documented during pregnancy were significantly lower than those recorded during anestrus, and a variation in the heart rate circadian rhythm was also found, as demonstrated by decreases at night and rises during the day. Cardiac rhythm had a similar performance in both pregnancy and anestrus. Likewise, the blood pressure, electrocardiography, and echocardiography data did not vary during the estrous cycle. The results support the role played by the autonomic nervous system during these two distinct periods in order to attain a heart rate that provides the blood needed by the female's body during the various stages of the reproductive cycle. Further studies are needed to better clarify the cardiovascular compensatory neuroendocrine events that accompany gestation in this species.
Keywords: Bitches; Cardiac parameters; Cardiovascular system; Dog; Estrous cycle; Pregnancy; Reproductive cycle